Listening In A Multicultural Reading of the Psalms - Reid, Stephen Breck (Nashville Abingdon Press, 1997)
"Every reader of the biblical text, Stephen Breck Reid contends, places it in the context of other texts and narratives, whether they be the stories of the reader's own experiences, or the broader myths and communal narratives of their culture. The valu
Keywords: Bible. -- Psalms -- Criticism, interpretation, etc. Multiculturalism -- Religious aspects -- Christianity. Minorities -- Religious life -- United States. Bible. -- Psalms. Minorities -- Religious life. United States. Bibel -- Psalmen